Effect of temperature and light on Germination Of Bermudagrass ( Cynodon Dactylon (L.) Pers.) seeds - Chan, Su Yi (Universiti Malaysia Sabah, 2017)
A study was conducted at the Faculty of Sustainable Agriculture, Universiti Malaysia Sabah, to investigate the effect of temperature and light on seed germination of Cynodon dactylon (L.) Pers. This study was arranged in a Completely Randomized Design (CRD), with 4 replicates for each treatment. Temperatures used in this study were ambient environment ( ± 24 °C), alternating temperature of 30/20 °C, 20 °C, 25 °C and 30 0 C. Germinating seeds were exposed to different light levels comprising 24 hours light, 24 hours darkness and alternating 12 hours light and 12 hours dark. Parameters evaluated in this study included germination percentage, plumule length, radide length, seedling length, seedling fresh and dry weight, germination index as well as seedling length vigour index. Significant interactions between temperature and light were observed in this study. Optimum germination occurred at an alternating 30/20 °C temperature regime and alternating light level with highest final germination percentage (92.75 %), radide length (1.71 cm), germination index (13.25) and seedling length vigour index (275.86). Temperature regime of 20 °C under continuous dark condition produced the poorest germination performance with only 2.5 % of seeds germinated for 7 days since the start of germination. This treatment also resulted the lowest germination index with only 0.36 and 2.52 of seedling length vigour index. No significant interaction was observed in seedling fresh and dry weight. Increasing temperature from 24 °C (ambient) to 30 °C resulted in increase of germination percentage, plumule length, radicle length, seedling length, seedling fresh and dry weight, germination index as well as seedling length vigour index.